Effects on Load-Frequency Control of a Solar Power System with a Two-Area Interconnected Thermal Power Plant and its Control with a New BFA Algorithm - Civelek, Zafer; Gorel, Goksu; Luy, Murat; Barısci, Necaattin; Cam, Ertugrul (Elektronika ir Elektrotechnika, 2018)
A control operation is the most important part of stabilization between load and frequency in a power system. The demand power change and the generated power change can disrupt the load-frequency balance. For this reason, the system frequency value should be controlled by some methods. In this study, a load frequency control was performed in a two-area power system. The renewable solar energy system and the interconnected power system were connected. In order to control the load-frequency balance, the classical PI, PID, Fuzzy Logic Controller (FLC) based PI and Bacterial Foraging Algorithm (BFA) based PI controller were separately designed and implemented to control the frequency value. All the trials were simulated and confirmed by the MATLAB/Simulink program. According to the results obtained from the control methods, the BFA-PI method provided better overshoots and BFA-PI had better settling times than the others.DOI: http://dx.doi.org/10.5755/j01.eie.24.6.22281